Remembering the Romanian Anti-Communist Armed Resistance: An Analysis of Local Lived Experience - Ciobanu, Monica (Eurostudia, 2015)
The anti-communist armed resistance that occurred as a disparate and heterogeneous movement in Romania from 1944 until 1962 became a highly politicized topic after 1989. Some interpreted this history as an element of the national resistance against Soviet occupation and the ensuing forced communization. Others demonized the partisans (or at least minimized their role) and presented them as outlaws, fascists, and criminals. This essay analyzes the armed resistance and its place within the politics of memory from three interrelated perspectives: 1) as lived experience in the context of post-World War II emergence of communism; 2) it takes a concretely localized perspective; and 3) analyzes these lived experiences as they have been presented in autobiographical accounts heavily influenced by post-1989 anti-communist rhetoric. The article concludes that multiple histories of repression and resistance have so far tended to be incorporated in a master narrative and argues that an approach emphasizing localized lived experience may offer an alternative interpretative framework.